Rising bubble simulations using lattice Boltzmann method coupled with level set interface capturing. Issue 1 (December 2014) - Safi, Mohammad Amin; Turek, Stefan
Abstract A multiphase Lattice Boltzmann (LB) scheme coupled with a level set interface capturing module is used for the simulation of multiphase flows, and in particular, rising bubbles under moderate and high density and viscosity ratios. We employ a consistent, robust discretization of the pressure forces which enables us to preserve stability and accuracy. The accuracy of the present scheme is shown to be competitive with that of the benchmark data from the finite element solutions in [3]. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)